Autoestima de mulheres mastectomizadas : aplicação da escala de Rosenberg - Santos, Míria Conceição Lavinas (2013)
The study aimed to identify the variables that influence the self-esteem of mastectomized women and assess their self-esteem level through the implementation of the Rosenberg Self-Esteem Scale. Exploratory, descriptive cross-sectional research carried out in July 2009 with 14 women of a support group in Fortaleza-CE, Brazil. Data were collected through semi-structured interview and application of this scale. The results showed an average age of 59 years, average time of 84.9 months after mastectomy and average time of support group of 59 months. Six (42.9%) women were married, 13 (92.9%) were religious and employed. The individual scores obtained with the Rosenberg scale showed high self-esteem among women. The assessment of self-esteem of mastectomized women can assist the adoption of nursing interventions capable of changing the type of care provided to these clients.